THE DESIGN AND IMPLEMENTATION OF VIRTUAL LABORATORY APPLICATION ON OPTICAL LENSE MODULE TO HELP DELIVERING THEORY IN PHISICS'S LABORATORY - Parno, Parno; Dharmayanti, Dharmayanti; Nindita, Dwitya Putri (Universitas Gunadarma, 2008)
Utilization of information technology in education is an effective means to improve the quality of student learning. Instance, developed learning modules for student, so the student can using virtual instruments. Learning modules that developed on the Basic Physics Laboratory called Optic Lens modules, it used for student learning, where reflected of the shadow of the object can not be captured by the display or can not be seen directly by eye, then the size can not be calculated due to limited human vision and the tools laboratory work. Therefore, developing application with java for visualization of thin lens can be expected to be a substitute tools.Keyword(s) : module, optic fiber, virtualSubject Description : J.2 Physical Sciences and Engineering | Physics | General